PENERAPAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIIA1 MTs DAREL HIKMAH PEKANBARU - Hurrahma, Mifta; Yuanita, Putri; Maimunah, Maimunah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The article explain about researchs to improve the learning process and mathematical problem solving skill of grade VII students with the implementation of realistic mathematics education approach. This type of this research is classroom action research with two cycle. This research was conducted in the in the second semester of academic year 2017/2018. Subjects were 25 female students of class VIIA1 MTs Darel Hikmah Pekanbaru. The research instrument consists of learning instruments and instruments of collecting data. The Learning instruments used include syllabus, lesson plans, and student activity sheets. While the instruments of collecting data covered: observation sheet were used to find out the data of students and teacher activity during learning process, and problem solving test were used to collect the student’s mathematical problem solving skill data. After analysis of implementing the realsitic mathematics educations on students and teacher activity, it can be concluded there was an improvement of learning process at each cycle. While analysis of problem solving test data, the mean of the student’s learning achievement had improved 29.53% from pre-cycle to cycle I and 18.67% from cycle I to cycle II. The improvement of student’s learning achievement founded four each indicator of mathematical problem solving skill. This study concludes that the implementation of realistic mathematics educations improved the learning process and mathematical problem solving skill at class VIIA1 MTs Darel Hikmah Pekanbaru.Key Words: Realistic mathematics educations, mathematical problem solving skill, learningactivity